Predictive performance of aldosterone-to-renin ratio in the diagnosis of primary aldosteronism in patients with resistant hypertension - Bioletto, Fabio; Lopez, Chiara; Bollati, Martina; Arata, Stefano; Procopio, Matteo; Ponzetto, Federico; Beccuti, Guglielmo; Mengozzi, Giulio; Ghigo, Ezio; Maccario, Mauro; Parasiliti-Caprino, Mirko (Frontiers in Endocrinology, 2023)
Background. The systematic use of confirmatory tests in the diagnosis of primary aldosteronism (PA) increases costs, risks and complexity to the diagnostic work-up. In light of this, some authors proposed aldosterone-to-renin (ARR) cut-offs and/or integrated flow-charts to avoid this step. Patients with resistant hypertension (RH), however, are characterized by a dysregulated renin-angiotensin-aldosterone system, even in the absence of PA. Thus, it is unclear whether these strategies might be applied with the same diagnostic reliability in the setting of RH. Methods. We enrolled 129 consecutive patients diagnosed with RH and no other causes of secondary hypertension. All patients underwent full biochemical assessment for PA, encompassing both basal measurements and a saline infusion test. Results. 34/129 patients (26.4%) were diagnosed with PA. ARR alone provided a moderate-to-high accuracy in predicting the diagnosis of PA (AUC=0.908). Among normokalemic patients, the ARR value that maximized the diagnostic accuracy, as identified by the Youden index, was equal to 41.8 (ng/dL)/(ng/mL/h), and was characterized by a sensitivity and a specificity of 100% and 67%, respectively (AUC=0.882); an ARR > 179.6 (ng/dL)/(ng/mL/h) provided a 100% specificity for the diagnosis of PA, but was associated with a very low sensitivity of 20%. Among hypokalemic patients, the ARR value that maximized the diagnostic accuracy, as identified by the Youden index, was equal to 49.2 (ng/dL)/(ng/mL/h), and was characterized by a sensitivity and a specificity of 100% and 83%, respectively (AUC=0.941); an ARR > 104.0 (ng/dL)/(ng/mL/h) provided a 100% specificity for the diagnosis of PA, with a sensitivity of 64%. Conclusions. Among normokalemic patients, there was a wide overlap in ARR values between those with PA and those with essential RH; the possibility to skip a confirmatory test should thus be considered with caution in this setting. A better discriminating ability could be seen in the presence of hypokalemia; in this case, ARR alone may be sufficient to skip confirmatory tests in a suitable percentage of patients.